ANALISIS MENEMBAK (SHOOT UNDER RING) BOLA BASKET ANGGOTA EKSTRAKURIKULER BOLA BASKET SMA NU KAPLONGAN - Arif Putra Septiandani; Riki Ramadhan; Fauzan Effendy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the shooting-under-the-ring ability of students participating in the basketball extracurricular program at SMA NU Kaplongan. The research employed a descriptive design using a test-based method. The population consisted of students enrolled in the basketball extracurricular activity, with a total of 11 participants serving as the research subjects. The instrument used was a performance test developed based on predetermined indicators. Data were analyzed using descriptive statistical techniques. The findings indicate that the majority of participants demonstrated a moderate level of shooting-under-the-ring ability. Specifically, 4 students (45%) were classified in the moderate category, 2 students (10%) in the good category, 3 students (35%) in the poor category, and 2 students (10%) demonstrated a very good level of performance.